2022
DOI: 10.1073/pnas.2208506119
|View full text |Cite
|
Sign up to set email alerts
|

FLASH X-ray spares intestinal crypts from pyroptosis initiated by cGAS-STING activation upon radioimmunotherapy

Abstract: DNA-damaging treatments such as radiotherapy (RT) have become promising to improve the efficacy of immune checkpoint inhibitors by enhancing tumor immunogenicity. However, accompanying treatment-related detrimental events in normal tissues have posed a major obstacle to radioimmunotherapy and present new challenges to the dose delivery mode of clinical RT. In the present study, ultrahigh dose rate FLASH X-ray irradiation was applied to counteract the intestinal toxicity in the radioimmunotherapy. In the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…3a, b), since mitochondrial DNA accounts for only 0.25% of the whole human cellular DNA 38 . In the prior investigations conducted by Shi et al 13 involving FLASH X-rays irradiation (120 Gy/s), a significant reduction in cytosolic dsDNA of intestinal organoids was observed through PicoGreen fluorescence quantification, which is a much stronger indicator than what we observed. Nevertheless, the normal human breast cell line MCF-10A used for our study is immortalized rather than the primary cells isolated from animal tissues, such that genes involved in cell cycle regulation, apoptosis, or DNA repair may exhibit elevated expression levels, and increase the intrinsic genome instability.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…3a, b), since mitochondrial DNA accounts for only 0.25% of the whole human cellular DNA 38 . In the prior investigations conducted by Shi et al 13 involving FLASH X-rays irradiation (120 Gy/s), a significant reduction in cytosolic dsDNA of intestinal organoids was observed through PicoGreen fluorescence quantification, which is a much stronger indicator than what we observed. Nevertheless, the normal human breast cell line MCF-10A used for our study is immortalized rather than the primary cells isolated from animal tissues, such that genes involved in cell cycle regulation, apoptosis, or DNA repair may exhibit elevated expression levels, and increase the intrinsic genome instability.…”
Section: Discussioncontrasting
confidence: 43%
“…1e are obtained by using the single-hit, multi-target model 31 SF=1-(1exp(-kD)) n , the fitting parameters (k, n) for MCF-10A, MDA-MB-231, and 4T1-luc cell lines are (0.46, 2.94), (0.63, 2.43), and (0.49, 1.91), respectively. The cGAS-STING activation post electron irradiation was investigated to find out the potential dose rate impact, as reported by Shi et al in their FLASH X-ray experiments 13 . The fluorescence intensity of the cytosolic dsDNA extract was normalized to that of the corresponding whole-cell extract under irradiation with different dose rates.…”
Section: Irradiation Experiments With Controllable Dose Rate and Dose...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruan et al found improvements in crypt survival and fewer changes to the microbiota after FLASH irradiation with a 6 MeV electron linear accelerator [ 34 ]. Ultra-high dose rate photon irradiation reportedly reduced intestinal pyroptosis and attenuated abdominal toxicity [ 35 ]. Less mortality was also observed following proton FLASH exposure when the mouse was placed either in the plateau region before the Bragg peak or within the spread-out Bragg peak (SOBP) [ 13 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although FLASH has been intensively researched, the mechanism is still subject to debate, including oxygen depletion (Jansen et al 2021), radical recombination (Labarbe et al 2020), change in endogenous reactive oxygen species (ROS) (Spitz et al 2019, Sultana et al 2022, immune response (Wilson et al 2020), radiation induced genomic instability (Shi et al 2022). The organisms damage from ionizing radiation primarily by shattering the DNA structure, which can be classified into direct damage and indirect damage.…”
Section: Introductionmentioning
confidence: 99%